INTERNAL ORGANS OF 5 WEEKS OLD QUAILS (Coturnix-coturnix japonica) GIVEN DIFFERENT LEVELS OF DRAGON FRUIT PEEL JUICE THROUGH DRINKING WATER - I. B. A., Dyatmika; Dewi, G. A. M. K.; Warmadewi, D. A. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the internal organs of quail given different levels of dragon fruit peel juice through drinking water. The design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replications, each replication consisting of 5 quails. The treatment given was drinking water without dragon fruit peel juice (P0), drinking water given 3% dragon fruit peel juice (P1), drinking water given 4% dragon fruit peel juice (P2), drinking water given 5% dragon fruit peel juice (P3). Variables considered included slaughter weight, heart percentage, liver percentage, kidney percentage, gizzard percentage, and cecum percentage. The results showed that the administration of  3%, 4% and 5% dragon fruit peel juice had a significantly different the percentage of the cecum  percentage and had no significant effect on slaughter weight  l oss , heart, liver, kidney and gizzard percentage. Based on this study, it can be concluded that quail treated with dragon fruit peel juice levels of 3%, 4%, and 5% through drinking water did not have an effect on slaughter weight, heart percentage, liver percentage, kidney proportions, and gizzard proportions, but had an effect to the proportion of the cecum.